2022
DOI: 10.1155/2022/6974681
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Selected Grass Species for Agronomic Performance, Forage Yield, and Chemical Composition in the Highlands of Ethiopia

Abstract: The study was conducted to determine the effect of different grass species (Brachiaria mutica, Desho, and Napier) and harvesting stages on agronomic performance, forage dry matter yield, and chemical composition. The grass species used were Desho (Pennisetum pedicellatum), Brachiaria (Brachiaria mutica), and Napier (Pennisetum purpureum), and the harvesting stages considered were 60, 90, and 120 days after establishment of grasses, respectively. The data collected included the following: percent plant survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
3
3
2
Order By: Relevance
“…In addition to its DM yield, B. mutica had the highest CP yield among the tested cultivars. Te dry matter yield of forage Brachiaria mutica (DZF-483) obtained in our results (13.2 t•ha −1 ) was comparable to the result (13.3 t•ha −1 ) reported during its variety registration [34] and higher than the result of 11.8 t•ha −1 that was reported in the northwest highlands of Ethiopia by Bantihun et al [35].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition to its DM yield, B. mutica had the highest CP yield among the tested cultivars. Te dry matter yield of forage Brachiaria mutica (DZF-483) obtained in our results (13.2 t•ha −1 ) was comparable to the result (13.3 t•ha −1 ) reported during its variety registration [34] and higher than the result of 11.8 t•ha −1 that was reported in the northwest highlands of Ethiopia by Bantihun et al [35].…”
Section: Discussionsupporting
confidence: 82%
“…In this study, all cultivars had CP concentrations >7%, which met the minimum crude protein requirements (7%) for the synthesis of microbial proteins in the rumen that can support at least the maintenance requirements of ruminants [40]. Te CP concentration for Brachiaria mutica in our study was slightly higher than the result of 11.6, reported by Bantihun et al [35]. Te B. decumbens Desho and Rhodes cultivars were also higher than the result reported by Faji et al [36] in Holetta under irrigation supplementation.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…The percentage of surviving plants in this study is comparable with the result reported by Wamatu (2021) [28], who observed a 100% survival rate for Desho grass. However, the current result is higher than that reported by Bantihun et al (2022) [29], who noted that the survival rate of Desho grass was 92.7%. This difference might be due to environmental conditions.…”
Section: Agronomic Performance Of Desho Grass Varietiescontrasting
confidence: 86%
“…Most improved and climate-resilient grass and legume species were recently selected and evaluated in various parts of the country for sustainable animal raising and environmental management [14,19,[21][22][23][24][25][26][27][28][29]. Improved fodder and forage production are the options for better feeding in climate-changing scenarios because they increase efciency with minimal eforts, beneft the degraded environment, reduce food competition, increase climate adaptation capacity, and reduce vulnerability to recurrent climate change and drought [29].…”
Section: Introductionmentioning
confidence: 99%